Eği̇ti̇mi̇n ticarileşmesi̇ ve kadın öğretmenleri̇n deği̇şen konumu - Sarıtepe, Selin (My University, 2023)
Türkiye’de tarihsel süreç içerisinde kapitalizmin uluslararası dönüşüm dinamikleri göz önüne alınarak kadın emeğinin eğitim sektöründeki değişen konumları inceleme alanı olmuştur. Eğitim insanlık tarihi boyunca toplumsal yapının önemli bir ögesi olmuştur ve değişikliklere uğramıştır. Kapitalistleşme ve modernleşme eğitimin değişimini hızlandırmıştır. Keyneysen dönemde mahiyeti farklı olan eğitimin sosyal hak olma olgusu 1980’li yıllarla başlayan neoliberal politikalar dalgasıyla eğitimin ticarileşmesi şeklinde dönüşüm yaşamıştır. Eğitim sektöründe çalışan öğretmenlerde bu süreçte gerek çalışma koşulları gerekse mesleklerinin toplumsal mahiyeti açısından önemli dönüşümlere uğramıştır. Özel okul sayıları her geçen gün artmıştır. Öğretmenden farklı biçimlere bürünen öğretmenler gerçeğine bir dönüşüm olmuştur. Öğretmenlik tarihsel olarak cinsiyetçi bir bakışla kadınlara özgü bir meslek olarak görülmüştür. Bu çalışmada ticarileşen ve metalaşan eğitim alanında kadın öğretmenlerin çalışma koşulları ve kadın olmaktan kaynaklanan ayrımcılığa dayalı konumları tartışmaya konu edilmiştir.

It has become an area of examination of the changing positions of women's labor in the education sector, taking into account the international transformation dynamics of capitalism in Turkey throughout the historical process. Education has been an important element of social structure throughout human history and has undergone changes. Capitalization and modernization have accelerated the change in education. The phenomenon of education being a social right, which had a different nature in the Keyney period, was transformed into the commercialization of education with the wave of neo-liberal policies that started in the 1980s. Teachers working in the education sector have undergone significant transformations in terms of both their working conditions and the social nature of their profession. The number of private schools has increased day by day. There has been a transformation from teachers to the reality of teachers taking on different forms. There has been a transformation from teachers to the reality of teachers taking on different forms. Teaching has historically been viewed from a sexist perspective as a profession reserved for women. In this study, the working conditions of female teachers in the commercialized and commoditized field of education and their positions based on discrimination due to being women are discussed.
Commercialization of education and the changing position of women teachers
Keywords: Kadın öğretmenler; Kadın öğretmenler Special education; Kitle eğitimi; mass education; Özel eğitim; Women teachers